Shamanic Culture's Reconnection of Earth and Heaven (Xu Ditiantong) in the New Era in China: The Dialectical Relationship between Material Civilization and Cultural Intimacy - Liu, Xiaoshuang (Religions, 2023)
Shamanic culture, which adheres to the worldview of connecting earth and heaven, has been marginalized in the discourse of the modern material world and separated from mainstream society. However, with the increase in personal problems in civil society and the rise of regional cultural identity since the reform and opening up in China, shamanic practitioners have again become active. Adapting to the official ideology, shamanic culture has emerged in China as a new form of folk culture and cultural heritage. Using Michael Herzfeld’s theory of “cultural intimacy” to a limited extent, this paper regards the new image of the shamanic tradition that has appeared in the new era as a manifestation of “cultural intimacy”, which does not infringe the authority of official discourse, nor damage the interests of government departments, and is in line with the imagination of official discourse about culture. Within the shaman cultural community, the shamanic tradition continues to connect earth and heaven, helping to solve difficult personal problems, alleviating the pressure of the material world, and at the same time making the sacred expression of the members of the shaman cultural community possible. In this way, the shaman tradition, which has emerged in a new image since the new era, has maintained the ecological balance between government and folk practices and formed a more stable pattern of cooperation.